1994
DOI: 10.1177/000456329403100503
|View full text |Cite
|
Sign up to set email alerts
|

Methodological and Clinical Aspects of Cyclosporin Monitoring: Report of the Association of Clinical Biochemists Task Force

Abstract: Additional key phrases: immunosuppressant drugs; analytical methods; transplantationDuring the last decade a growing number of centres have become involved in the measurement of the immunosuppressive agent cyclosporin, When the UK Cyclosporin Quality Assessment Scheme (UKCQAS) was started by two of us (DH and AI) in 1984 there were 14 participants in the UK; now there are over 50. The increasing number of indications for which cyclosporin can be prescribed, together with the proliferation of centres capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 101 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…0 mmoles/liter; 4) CsA trough levels >200 ng/ml, measured on whole blood using the specific monoclonal antibody radioimmunoassay method (30); and/or 5) systolic or diastolic blood pressure to 160 or 95 mm Hg at 2 consecutive visits. A temporary or permanent increase in dosage was allowed in the event of poor treatment efficacy according to the investigator's global evaluation (up to a maximum of 5 mg/kg/ day).…”
Section: Methodsmentioning
confidence: 99%
“…0 mmoles/liter; 4) CsA trough levels >200 ng/ml, measured on whole blood using the specific monoclonal antibody radioimmunoassay method (30); and/or 5) systolic or diastolic blood pressure to 160 or 95 mm Hg at 2 consecutive visits. A temporary or permanent increase in dosage was allowed in the event of poor treatment efficacy according to the investigator's global evaluation (up to a maximum of 5 mg/kg/ day).…”
Section: Methodsmentioning
confidence: 99%
“…7 To meet these challenges, relatively aggressive immunosuppressive regimens are employed in lung transplantation patients compared with renal or liver transplantation. 8 Currently, a triple immunosuppressive regimen, consisting of a calcineurin inhibitor, steroids and mycophenolate mofetil or azathioprine, is standard at most centers. 4 However, efforts continue to identify improved immunosuppressive strategies that reduce the high incidence of rejection after lung transplantation without exposing patients to additional adverse events, particularly infectious complications that occur with a greater frequency in this population than in recipients of any other type of solid organ allograft, 9 and which are a considerable source of morbidity and mortality.…”
mentioning
confidence: 99%
“…While oral administration is the preferred route of CsA prophylaxis, its absorption may be incomplete, slow and erratic thus suggesting a major drawback of oral formulation. The bioavailability of oral CsA averages about 30% (Holt et al, 1994) and large inter-and intrapatient variations in CsA absorption have been observed partly due to the unpredictable bioavailability of CsA following oral administration. These variations most likely reflect differences in the seperation of CsA from its vehicle in the intestine.…”
Section: Pharmacokineticsmentioning
confidence: 99%